Chelsea London: capstone - London, Chelsea, artist (Colorado State University. Libraries, 2014)
The artist's statement: As an artist, I work hard to develop pieces that are both simple and yet, at the same time, intricately detailed. Part of my process before I begin is to absorb as much from the world around me - everything and anything can spark inspiration. I try with every finished work to breathe story into line and color so that my designs, ideas, and concepts live and captivate one's attention.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.